The Role of Human Resource Management Practices in theSurvival of Core EmployeesA field study in the cellular communication company MTN (Damascus University Journal for the economic and Political sciences, 2025)
The study aimed to test the role of human resource management practices (organization culture, work environment, leadership style, employee empowerment) in the survival of core employees in MTN cellular communication company. To achieve the aim of the study, the researcher designed a questionnaire to collect primary information from the research sample, which included (100) respondents from the company's employees. After conducting the analysis of the study data and hypotheses, the study concluded that human resource management practices in MTN Corporation affect the survival of core employees to a high degree, in addition to the existence of a statistically significant correlation between human resource management practices and survival of core employees.
Keywords: Human Resources Management Practices; Core Employees; MTN Compan